Novel wideband circularly polarized DRA with squint-free radiation characteristics - Mohammad Abedian (Nature Portfolio, 2021)
Abstract A new single-fed circularly polarized dielectric resonator antenna (CP-DRA) without beam squint is presented. The DRA comprises an S-shaped dielectric resonator (SDR) with a metalized edge and two rectangular dielectric resonators (RDRs) blocks. Horizontal extension section is applied as an extension of the SDR, and a vertical-section is placed in parallel to the metallic edge. A vertical coaxial probe is used to excite the SDR and the vertical RDR blocks through an S-shaped metal element and a small rectangular metal strip. The two added RDRs that form an L-shaped DR improve the radiation characteristics and compensate for the beam squint errors. A wideband CP performance is achieved due to the excitation of several orthogonal modes such as $$TE_{δ 11}^x$$ T E δ 11 x , $$TE_{1δ 1}^y$$ T E 1 δ 1 y , $$TE_{121}^z$$ T E 121 z , $$TE_{112}^y$$ T E 112 y , $$TE_{131}^x$$ T E 131 x , and $$TE_{311}^y$$ T E 311 y . The experimental results demonstrate an impedance bandwidth of approximately $$66.8%$$ 66.8 % (3.71–7.45 GHz) and a 3-dB axial-ratio (AR) bandwidth of about $$54.8%$$ 54.8 % (3.72–6.53 GHz) with a stable broadside beam achieving a measured peak gain of about $$4.64 \, {\text{dBic}}$$ 4.64 dBic . Furthermore, a 100% correction in beam squint value from $$θ = 41^°$$ θ = 41 ∘ to $$θ = 0^°$$ θ = 0 ∘ with respect to the antenna boresight is achieved.